2008
DOI: 10.1097/mpa.0b013e31818166d2
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Survival (5-20 Years) After Pancreatectomy for Pancreatic Ductal Adenocarcinoma

Abstract: Pancreatic duct adenocarcinoma can be cured, and long-term survival after R0 curative surgery has become a reality. Long-term survivors did not fulfil the ideal prognostic criteria and even presented with advanced stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 43 publications
1
49
1
1
Order By: Relevance
“…Surgical resection is the standard of care for patients with tumours confined to the head of the pancreas [1][2][3]. An increasing number of reports attest that pancreaticoduodenectomy can be performed with low operative mortality [2,4].…”
Section: Introductionmentioning
confidence: 99%
“…Surgical resection is the standard of care for patients with tumours confined to the head of the pancreas [1][2][3]. An increasing number of reports attest that pancreaticoduodenectomy can be performed with low operative mortality [2,4].…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13] Clinicopathological features associated with improved survival at 5 years post-resection include small tumor size (< 2 cm), negative lymph node status, negative resection margin (i.e., R0), absence of angiolymphatic and perineural invasion, and low grade of differentiation. Relatively longer (i.e., ≥ 5 y) survival after surgery for PDAC has been increasing for the last two decades, largely due to centralization of surgery to high-volume (i.e., expert) centers.…”
Section: Introductionmentioning
confidence: 99%
“…11,[19][20][21] Nonetheless, there are a handful of published studies which have identified ≥ 10-y survivors of histologically validated PDAC, usually at a frequency less than 5% in most series. 4,5,12,22 Of note, these cohorts of VLTS patients not only include those with small T1, node-negative (N0) tumors, but also patients with more aggressive features, including T2-T4 sized lesions, and lymph node involvement. 5 This would suggest that the basis of VLTS in PDAC extends beyond simply resecting node-negative localized cases, but might indicate an intrinsic molecular phenotype of such tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Underpinning this trend is the fact that pancreatic cancer tends to present late and that complete surgical resection still offers the best chance of disease-specific survival [3,14,15]. Indeed, various papers have reported improved 5-year survival rates of between 12% and as high as 27% after resection in recent years [16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have showed improved survival [28], with some quoting comparable 5-year rates of [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35].5% [29][30][31]. In contrast, other studies have demonstrated a significant difference in favor of the standard resection group.…”
Section: Long-term Outcomesmentioning
confidence: 99%